Vocabulary Learning Through Educational Animation: A Formative Evaluation of ’Learn with Voca’ for Elementary Learners - Che Omar, Azizah; Yusof, Norhana; Abd Muin, Mohd Adib (Journal of Advanced Research Design, 2025)
The acquisition of English language skills is essential for elementary students; however, many learners encounter challenges such as limited vocabulary, difficulties in pronunciation, and inadequate writing skills. To address these issues and foster greater interest in learning English, this study focuses on the development of a 2D animation video titled Learn with Voca. The primary aim is to facilitate English language learning by providing engaging and accessible visual content that helps students better understand, recognize, and use English vocabulary effectively. This study has two main objectives: (1) to develop the Learn with Voca 2D animation video, and (2) to evaluate Learn with Voca 2D animation video through expert reviews. The evaluation methodology involved presenting a high-fidelity prototype of the animation to subject-matter experts, followed by structured interviews to gather feedback, suggestions, and recommendations for improvement. The findings reveal that the majority of experts positively endorsed the animation’s content and storyline, highlighting its potential to capture students’ attention, enhance engagement, boost motivation, and support classroom learning. Experts also agreed that Learn with Voca is appropriate for elementary-level students and can serve as an effective instructional tool for educators.